STUDENTS’ ANXIETY IN SPEAKING ENGLISH IN THE CLASSROOM - I Dewa Ayu Anom Budayanti; I Gede Yoga Permana; Nyoman Canestra Adi Putra (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2023)
The purpose of this study is to determine the level of students' anxiety as well as the elements that contribute to their anxiety when speaking in English. This survey study employed the FLCAS (Foreign Language Classroom Anxiety Scale) questionnaire by Horwitz et al. (1986) and interviews. Sixty students were chosen as the sample of the study. The results showed 20% of participants feel very anxious, 42% feel anxious level, 23% feel mild anxious, 8% feel relaxed, 5% feel very relaxed. In the interview, the types of language anxiety indicators were also identified. The results show that fear of negative evaluation and feeling insecure were the major causes of students’ anxiety. This study implied that anxiety could become a driving factor that leads students to be passive and make no effort to speak English in the classroom.  Teachers are encouraged to address students’ anxiety in order to help students overcome their anxiety.